Peran Pola Asuh Orang Tua terhadap Kecemasan Sosial pada Remaja - Fitria Rachmawaty (University of Merdeka Malang, 2015)
The purpose of this study was to determine the role of parenting on social anxiety in adolescents. This study involved 230 adolescents with authoritarian parenting with an average 30.37. Retrieval of data using Parental Authority Questionnaire (PAQ), Liebowitz Anxiety Scale- Children and Adolecents (LSAS-CA). Significance test shows F count 107.678. Significant conclusion of this model and can be used to predict the role of authoritarian parenting to social anxiety in adolescents. The result showed that social anxiety in adolescents can be affected by direct authoritarian parenting.